LA TRADUCCIÓN EN LAS PUBLICACIONES PERIÓDICAS DE IZQUIERDA EN CHILE: ITINERARIOS DE UNA PRÁCTICA (1911-1932). - Concha-Ferreccio, Pablo; Errázuriz-Cruz, Rebeca (Revista Chilena de Literatura, 2024)
This article delves into the translation practices within three paradigmatic magazines of the 1920s Chilean generation: Juventud, Numen, and Claridad. Its primary aims are to systematically characterize the newly compiled corpus for the first time and to contemplate the inherent challenges associated with translation as a cultural mediation practice. These challenges encompass the ramifications of linguistic hegemonies, the distinctive attributes of authorial figures, the practice of clipping translations, and the intellectual networks interwoven with these issues.